Research advances in disinfection and inactivation methods for norovirus - Surui JIANG; Huiying LI; Zhaojun DUAN (Editorial Office of Chinese Journal of Public Health, 2024)
Norovirus is a leading cause of acute gastroenteritis in humans worldwide. Norovirus infection is characterized by low infectious dose, high viral shedding, strong environmental resistance and multiple modes of transmission, making it difficult to prevent and control. To date, there are no targeted vaccines or drugs for the specific treatment and prevention of norovirus infection, which represents a major challenge and threat to global public health. Therefore, rapid and efficient virus inactivation and effective interruption of pathogen transmission routes are of great importance for successful prevention and control of norovirus infections and outbreaks. This article reviews the disinfection and inactivation methods for norovirus and their applications from 2000 to 2023, providing a reference for the adoption of scientific and effective interdiction measures to reduce the risk of human infection with norovirus.